An economical and efficient method for postmortem DNA sampling in mass fatalities. (September 2018) - Mundorff, Amy Z.; Amory, Sylvain; Huel, René; Bilić, Ana; Scott, Audrey L.; Parsons, Thomas J.
Highlights: Postmortem swabs transferred to FTA ® cards can streamline disaster victim identifications. Total Body Score (TBS) can be a quick field assessment to evaluate the degree of body decomposition. No relationship exists between Accumulated Degree Days (ADD) and DNA degradation. A TBS of 13 and below consistently yielded a full profile regardless of the sampling season or ADD. Abstract: In mass fatality events, the need to identify large numbers of deceased persons using DNA can be a significant drain on already overburdened forensic practitioners, both in the field setting and the laboratory. The laboratory may be required to extract DNA from a variety of postmortem sample types, family or direct reference samples related to the missing, and perform matching of these results in a short period of time. While most forensic institutions are well equipped to handle both family and direct reference samples, postmortem samples such as bone or heterogeneous tissue samples can be difficult for labs to analyze. We have devised an easily deployable, efficient, and inexpensive method for collecting postmortem DNA samples on commercially available DNA preservation cards ("FTA ® " cards). FTA ® cards are already widely used in forensic labs and are convenient for shipping due to their small volume and stability at room temperature. We evaluated the suitability of a protocol involving swabbing of incisions made on cadavers and sample deposition onto FTA ® cards over various postmortem intervals and under different environmental conditions. Each trial took place during a different point in the calendar year to evaluate the effects of seasonal weather patterns and temperature on decomposition, DNA yield, and rates of DNA degradation. To further account for the effects of seasonality (temperature and humidity), the progression of body decomposition was recorded following the Total Body Score (TBS) method [1]. DNA degradation was assessed either through STR amplification of 1.2 mm FTA punches or DNA extraction from 3.0 mm punches followed by real-time PCR quantification and STR amplification and genotyping. No consistent relationship was observed between postmortem interval and DNA degradation. Instead, the TBS score, which captures the stage of body decomposition, was shown to correlate well with DNA quantity. A TBS of 15 and below consistently yielded strong partial or full profiles (20 STR loci and Amelogenin using the PowerPlex 21 System) from all individuals from either 1.2 mm or 3.0 mm punches. Transfer of sample swabs to FTA cards is shown to be a simple and effective method for both field and laboratory operations over a range of conditions that can be evaluated by field forensic practitioners based on a body decomposition score. The approach could be beneficially integrated into mass fatality response plans.